Orthostatic Cognitive Dysfunction in Postural Tachycardia Syndrome After Rapid Water Drinking - Rodriguez, Belén; Zimmermann, Raya; Gutbrod, Klemens; Heinemann, Doerthe; Z’Graggen, Werner J. (Frontiers in Neuroscience, 2019)
Background. Postural Tachycardia Syndrome (POTS) is a form of autonomic dysregulation and is characterized by an excessive heart rate (HR) increment upon the upright body position while blood pressure is maintained. Patients experience typical symptoms of orthostatic intolerance such as dizziness, nausea and cognitive impairments. The present study assessed position-dependent attentional and cognitive functioning in POTS patients compared to healthy subjects and tested the response of cognitive performance to acute water intake. Methods. Data was obtained from 8 patients with neuropathic POTS and 8 healthy subjects of similar age and gender. All participants completed questionnaires that assessed health-related quality of life and depression and underwent four rounds of neuropsychological testing overall, each before and after the intake of 500 ml still mineral water and both in the supine and in the upright posture. Results. POTS patients showed deficits in working memory exclusively in the upright position compared to healthy subjects, but no position-dependent impairments in alertness or divided attention. Rapid water ingestion had a beneficial effect on working memory in the upright posture, lead to a decrease in HR increment and to an improvement of subjective symptom experience. Conclusion. The results provide support for the occurrence of purely orthostatic cognitive deficits in POTS, especially when increased executive control and cognitive resources are required and document a favorable effect of water intake on cognitive performance. These findings have important implications for the management of cognitive symptoms in POTS as high water intake is an easy and accessible strategy.